Efficacy of an inactivated EHDV-8 vaccine in preventing viraemia and clinical signs in experimentally infected cattle - Massimo Spedicato; Gaetano Federico Ronchi; Francesca Profeta; Sara Traini; Sara Capista; Alessandra Leone; Mariangela Iorio; Ottavio Portanti; Cristiano Palucci; Simone Pulsoni; Lilia Testa; Anna Serroni; et al. (Virus Research, 2024)
Epizootic haemorrhagic disease (EHD), caused by the EHD virus (EHDV), is a vector-borne viral disease transmitted through Culicoides biting midges. EHDV comprises seven serotypes (1, 2, and 4–8), with EHDV-8 having recently emerged and spread in Europe over the last two years. Such event has raised concerns about the significant threat posed by EHDV-8 to livestock industry. In this study, an inactivated vaccine against EHDV-8 (vEHDV8-IZSAM) was developed. Safety and efficacy of the vaccine were evaluated in calves through clinical, serological, and virological monitoring following experimental challenge.The vaccine was proven safe, with only transient fever and localized reactions observed in a few animals, consistent with adjuvanted vaccine side effects. vEHDV8-IZSAM elicited a robust humoral response, as evidenced by the presence of neutralizing antibodies. After challenge with a virulent isolate, viraemia and clinical signs were evidenced in control animals but in none of the vaccinated animals.This study highlights the potential of vEHDV8-IZSAM as a safe and highly effective vaccine against EHDV-8 in cattle. It offers protection from clinical disease and effectively prevents viraemia. With the recent spread of EHDV-8 in European livestock, the use of an inactivated vaccine could be key in protecting animals from clinical disease and thus to mitigate the economic impact of the disease. Further investigations are warranted to assess the duration of the induced immunity and the applicability of this vaccine in real-world settings. Accordingly, joint efforts between public veterinary institutions and pharmaceutical companies are recommended to scale up vaccine production.